The study of Algebra requires an intrinsic and deep understanding of formulas, terms and concept. Hence, to ease this task we provide to you “Algebra Formulas for class 10”, a thorough and complete guide exclusively drafted to boost the confidence of the students. All algebra formulas for class 10 in a single page format will help students to grasp and understand every concept thoroughly and solve problems easily.

The CBSE Class 10 mathematics consists algebra in many chapters like:

- Algebraic method of solving pair of linear equation - elimination method
- Algebraic method of solving pair of linear equation - substitution method
- Algebraic method of solving pair of linear equation - cross multiplication method

All these chapters will have many formulas. A student may feel difficult to note them and read. To make easy for them. All the important algebra formulas for class 10 are listed below.

Algebraic Identities For Class 10 |

\(\mathbf{(a+b)^{2}}\) \(=a^2+2ab+b^{2}\) |

\(\mathbf{(a-b)^{2}}\) \(=a^{2}-2ab+b^{2}\) |

\(\mathbf{\left (a + b \right ) \left (a – b \right ) }\) \( = a^{2} – b^{2}\) |

\(\mathbf{ \left (x + a \right )\left (x + b \right ) }\) \(= x^{2} + \left (a + b \right )x + ab\) |

\(\mathbf{\left (x + a \right )\left (x – b \right ) }\) \(= x^{2} + \left (a – b \right )x – ab\) |

\(\mathbf{\left (x – a \right )\left (x + b \right )}\) \(= x^{2} + \left (b – a \right )x – ab\) |

\(\mathbf{\left (x – a \right )\left (x – b \right ) }\) \(= x^{2} – \left (a + b \right )x + ab\) |

\(\mathbf{\left (a + b \right )^{3}}\) \( = a^{3} + b^{3} + 3ab\left (a + b \right )\) |

\(\mathbf{\left (a – b \right )^{3} }\) \(= a^{3} – b^{3} – 3ab\left (a – b \right )\) |

\(\mathbf{(x + y + z)^{2}}\) \( = x^{2} + y^{2} + z^{2} + 2xy + 2yz + 2xz\) |

\(\mathbf{(x + y – z)^{2}}\) \( = x^{2} + y^{2} + z^{2} + 2xy – 2yz – 2xz\) |

\(\mathbf{(x – y + z)^{2} }\) \(= x^{2} + y^{2} + z^{2} – 2xy – 2yz + 2xz\) |

\(\mathbf{(x – y – z)^{2}}\) \( = x^{2} + y^{2} + z^{2} – 2xy + 2yz – 2xz\) |

\(\mathbf{x^{3} + y^{3} + z^{3} – 3xyz }\) \( = (x + y + z)(x^{2} + y^{2} + z^{2} – xy – yz -xz)\) |

\(\mathbf{x^{2} + y^{2}}\) \( = \frac{1}{2} \left [(x + y)^{2} + (x – y)^{2} \right ]\) |

\(\mathbf{(x + a) (x + b) (x + c) }\) \(= x^{3} + (a + b +c)x^{2} + (ab + bc + ca)x + abc\) |

\(\mathbf{x^{3} + y^{3}}\) \(= (x + y) (x^{2} – xy + y^{2})\) |

\(\mathbf{x^{3} – y^{3}}\) \( = (x – y) (x^{2} + xy + y^{2})\) |

\(\mathbf{x^{2} + y^{2} + z^{2} -xy – yz – zx }\) \( = \frac{1}{2} [(x-y)^{2} + (y-z)^{2} + (z-x)^{2}]\) |

Linear Equation in Two Variables |

\(\mathbf{a_{1}x + b_{1}y + c_{1} }\) \(= 0\) |

\(\mathbf{a_{2}x+ b_{2}y + c_{2}} \) \(= 0 \) |